Using collaborative logic analysis evaluation to test the program theory of an intensive interdisciplinary pain treatment for youth with pain‐related disability - Karen Hurtubise; Astrid Brousselle; Chantal Camden (Wiley, 2020)
Abstract Intensive interdisciplinary pain treatment (IIPT) involves multiple stakeholders. Mapping the program components to its anticipated outcomes (ie, its theory) can be difficult and requires stakeholder engagement. Evidence is lacking, however, on how best to engage them. Logic analysis, a theory‐based evaluation, that tests the coherence of a program theory using scientific evidence and experiential knowledge may hold some promise. Its use is rare in pediatric pain interventions, and few methodological details are available. This article provides a description of a collaborative logic analysis methodology used to test the theoretical plausibility of an IIPT designed for youth with pain‐related disability. A 3‐step direct logic analysis process was used. A 13‐member expert panel, composed of clinicians, teachers, managers, youth with pain‐related disability, and their parents, were engaged in each step. First, a logic model was constructed through document analysis, expert panel surveys, and focus‐group discussions. Then, a scoping review, focused on pediatric self‐management, building self‐efficacy, and fostering participation, helped create a conceptual framework. An examination of the logic model against the conceptual framework by the expert panel followed, and recommendations were formulated. Overall, the collaborative logic analysis process helped raiseawareness of clinicians' assumptions about the program causal mechanisms, identified program components most valued by youth and their parents, recognized the program features supported by scientific and experiential knowledge, detected gaps, and highlighted emerging trends. In addition to providing a consumer‐focused program evaluation option, collaborative logic analysis methodology holds promise as a strategy to engage stakeholders and to translate pediatric pain rehabilitation evaluation research knowledge to key stakeholders.